1218 Frontal lobe activity during memory encoding in temporal lobe epilepsy. Issue 3 (9th February 2012) - Sidhu, M; Stretton, J; Winston, G; Vollmar, C; Bonelli, S; Thompson, P; Koepp, M; Duncan, J S
Abstract : Purpose: The contribution of the frontal lobes to memory encoding has been recently appreciated. Functional MRI (fMRI) studies have demonstrated material specific prefrontal cortex (PFC) activations with verbal and non-verbal memory tasks on the left and right respectively in healthy individuals. We investigated the patterns of PFC activations in memory encoding for both verbal and non-verbal episodic memory in Temporal Lobe Epilepsy (TLE) patients using fMRI. Methods: 27 healthy controls and 42 patients with hippocampal sclerosis (21 Right) were scanned on a 3T MRI scanner. An fMRI paradigm of memory encoding of faces and words was employed. fMRI analysis was performed with SPM8. Results: Word encoding: controls and right HS patients activated the left PFC. Patients with left HS showed bilateral HC activations and significant additional right PFC activations greater than in controls and the right HS group p<0.005. Face encoding: controls and LHS patients showed right lateralised PFC activation. Patients with right HS showed bilateral PFC activations. Significantly greater left PFC activation was seen in the right HS group compared to the left HS group (p<0.005). Conclusion: We showed material specific PFC lateralisation in healthy controls as previously described. Patients with HS ipsilateral to side of material encoding showed additional contralateral PFC activations, implying reorganisation of the underlying network to involve the contralateral frontal lobes.